Um rio chamado Jari: antropologia fluvial e etnografia multiespécies nas ruínas de um grande projeto na Amazônia - Teixeira, Daniel Bustamante (2025)
The thesis, resulting from extensive fieldwork, aims, through ethnographic accounts, to introduce the reader to a conceptual and sentient framework of an Amazonian way of life strongly connected to rivers and interspecific coexistence practices. In these practices, humans are not placed above other beings—whether plants, animals, entities, or rivers—but are rather embedded in a vital web of relationships. The goal is to relate the experiences and learnings from fieldwork to contemporary anthropological theory, particularly within the scope of what is known as multispecies anthropology. The thesis focuses on the river and the inhabitants of its banks in the municipality of Laranjal do Jari (AP). Situated at the intersection of land and water, urban and rural, as versatile and malleable as the thick mud that accumulates and dries on the shores, the residents of Laranjal do Jari stand out for their visceral relationship with the river that gives the city its name. Initially, the river is highlighted as a border between two states – Amapá and Pará – and between distinct urbanization models stemming from the same origin: the monumental Jari Project and its drastic impact on the region. Subsequently, the anthropologist's journey in search of their subject of analysis is described, during which distinctions between home and field dissolve, and they are affected by a flood, thus revealing different ways of relating to the river—both along its banks and in the hinterlands.The second part of the thesis stems from more recent and immersive fieldwork, during which the anthropologist accompanied a group of fishermen on a week-long expedition, among other experiences. Initially, Nova Esperança neighborhood in Laranjal do Jari and the igapó or island that provides land access to the Jari River in the summer, merging with it in the winter, are described, along with some of the residents' practices, such as tamatá fishing and piracaia. Finally, through the experience of fishing in the lakes of a former rice plantation, a story of resurgence from ruins is narrated, offering lessons that may prove valuable as we all learn to live in times of catastrophe. The results aim to position the Amazon at the center of a global discussion on climate and ecology, presenting, through interactions with inhabitants who have built their lives atop the remnants of grand projects, some ideas and alternatives for fostering habitability and envisioning possible futures in a world of ruins.